The Effect of Different Finishing Lines on the Marginal Fitness of Full Contour Zirconia and Glass Ceramic CAD/CAM Crowns (An in-vitro study) - ZAK Al-Zubaidi; AMW Al-Shamma (Mashhad University of Medical Sciences, 2015)
Purpose: The aim of this study was to evaluate the effect of two gingival finishing lines (90° shoulder and deep chamfer) on the marginal fitness of two types of full anatomic all-ceramic crowns; zirconia crowns (Zikonzhan) and glass ceramic crowns (IPS e-max CAD) milled with CAD/CAM system. Materials and Methods: Two dentoform teeth of left maxillary first molar were prepared with chamfer finishing line (CFL) and shoulder finishing line (SFL), respectively and duplicated to Nickel-Chromium master dies. Thirty two crowns were fabricated and grouped as follows: Group I: 8 zirconia crowns on CFL; Group II: 8 zirconia crowns on SFL; Group III: 8 glass ceramic crowns on CFL and Group IV: 8 glass ceramic crowns on SFL. Marginal gaps were measured at 4 indentations, each one was at center of each tooth surface and collectively 16 points were measured by using stereomicroscope (160X). The data were analyzed by One-way ANOVA and student t-tests. Results: Group I produced the least marginal gap (73.55µm); followed by Group II (92.60µm), and Group III (151.45µm) and the highest marginal gap was recorded by Group IV (162.34µm). Statistical analysis of the data showed that SFL produced significantly greater marginal gap on zirconia crowns in comparison with CFL. However, in glass ceramic crowns, CFL revealed less marginal gap compared to SFL but statistically was not significant. On the other hand, glass ceramic crowns significantly produced a greater marginal gap in comparison to zirconia crowns regardless type of finishing line. Conclusions: deep chamfer margin could be more preferable finishing line than 90° shoulder especially for zirconia full crowns. Furthermore, zirconia crowns could be more advisable than glass ceramic crowns in respect to marginal adaptation.